Administrative Investigation Of The Public Servant In Jordanian Legislation (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Administrative investigation is one of the guarantees guaranteed by various legislations, including Jordanian legislation for the public servant, where the administration adheres to it in accordance with the procedures legally specified, as a preliminary measure after committing the disciplinary violation by the public servant .    The Department is conducting a search to uncover the circumstances of the offence committed by the public servant, where it investigates the charge against him, to ensure that the truth is found after discussion.    That is, it is a measure taken by the Administration after the disciplinary offence and the commission by the public servant.